Aerospace materials handbook - Zhang, Sam; Zhao, Dongliang (Advanced in materials science and engineering, 2013)
The Aerospace Materials Handbook examines these materials, covering traditional superalloys as well as more recently developed light alloys. Capturing state-of-the-art developments in materials research for aeronautical and aerospace applications, this book provides a timely reference for both newcomers and veteran researchers in the field.